Neuroevolution under unimodal error landscapes : an exploration of the semantic learning machine algorithm - Jagusch, Jan-Benedikt (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence